Age at first alcoholic drink as predictor of current HIV sexual risk behaviors among a sample of injection drug users (IDUs) and non-IDUs who are sexual partners of IDUs, in St. Petersburg, Russia. - Abdala, Nadia; Hansen, Nathan B; Toussova, Olga V; Krasnoselskikh, Tatiana V; Kozlov, Andrei P; Heimer, Robert (AIDS and behavior, 2012)
This study investigates whether age at first alcoholic drink is associated with sexual risk behaviors among injection drug users (IDUs) and non-IDUs who are sexual partners of IDUs in St. Petersburg, Russia. A path analysis was used to test a model of age at first drink, age at sexual debut, age at first drug use, current substance use patterns and current sexual risk behaviors among 558 participants. Results revealed that age at first drink had an effect on multiple sex partners through age at sexual debut and injection drug use, but no effect on unprotected sex. Age at first drug use was not related to sexual risk behaviors. Investigation of age of drinking onset may provide useful information for programs to reduce sexual risk behaviors and injection drug use. Different paths leading to unprotected sex and multiple sexual partners call for different approaches to reduce sexual risk behaviors among this population.
Keywords: Adolescent; Adult; Age Factors; Alcohol Drinking; Drug Users; Female; HIV Infections; Humans; Interviews as Topic; Male; Middle Aged; Questionnaires; Risk-Taking; Russia; Sexual Behavior; Sexual Partners; Socioeconomic Factors; Substance Abuse, Intravenous; Young Adult